INNOVATIVE TECHNOLOGIES IN TEACHING THEORETICAL MECHANICS FOR AGRI-ENGINEERS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The article deals with innovative technologies of teaching theoretical mechanics for agro-engineering education. This discipline forms the basic engineering knowledge critical for the agro-industrial complex. In the context of digitalization, it is relevant to improve teaching methods using digital simulators, interactive platforms and adaptive online courses that visualize complex mechanical processes and facilitate the understanding of theoretical foundations. Special attention is given to the practice-oriented approach that allows students to apply knowledge in real engineering problems. The benefits of innovative technologies include: increasing the accessibility of educational material, developing analytical and engineering skills through simulations, reducing the burden on teachers by automating the verification of calculations, and developing the systemic thinking necessary to solve interdisciplinary problems. The results of the study showed that the integration of innovative technologies into the process of learning theoretical mechanics contributes to increasing the level of material assimilation by 30-40%, increasing student motivation by 30% and improving the quality of engineering calculations by 25% compared to traditional teaching methods. It is concluded that the introduction of innovative technologies in the teaching of theoretical mechanics allows optimising the educational process, making it more interactive, practical and adaptable to the individual needs of students. In order to further improve the quality of engineering education, it is recommended to strengthen interdisciplinary integration, to involve experts from the agro-industrial sector in the development of teaching materials, and to make more active use of digital educational ecosystems that ensure the continuous professional development of future specialists.